Application of capillary zone electrophoresis to determine second-generation H1 antihistaminic drugs, loratadine and rupatadine - Cintia Maria Alves Mothé; Aline de Souza; Anil Kumar Singh; Nádia Araci Bou-Chacra; María Segunda Aurora-Prado (Universidade de São Paulo, 2023)
Abstract The second generation of H1 antihistamines from the piperidine group are often used for treating allergic diseases due to their action on histaminic receptors, the primary mediator of allergy. Moreover, the antihistamines have anti-inflammatory action, mediated through platelet-activating factor blocking activity. A simple and rapid capillary zone electrophoresis method was developed and validated for the determination of loratadine (LOR) and rupatadine (RUP) in tablets. The analyses were carried out using a fused silica capillary of 50.2 cm (40 cm effective length), 75 µm i.d. The background electrolyte was composed of boric acid 35 mmol/L, pH 2.5. Voltage of 20 kV, hydrodynamic injection of 3447.3 Pa for 3s, temperature at 25 ºC, and UV detection at 205 nm were applied. Electrophoretic separation was achieved at 1.8 and 2.8 min for RUP and LOR, respectively. The method was linear for both drugs in a range of 50.0 to 400.0 μg/mL (r>0.99). The limits of detection and quantification were 46.37 and 140.52 μg/mL, for LOR and 29.60 and 89.69 μg/mL for RUP respectively. The precision was less than 5.0 % for both drugs. The average recovery was approximately 100 %. The proposed novel method can significantly contribute to the rapid detection of counterfeit products and in quality control of drug products containing antihistamines.